PENERAPAN MODUL PEMBELAJARAN VISUAL BASIC BERBASIS MODEL PROBLEM BASED LEARNING - Wiwita, Risma; Handayani, Revi; Efendi, Efendi; Vratiwi, Septiana; Efrianto, Efrianto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
The purpose of this research is to Visual Basic learning modules and Problem Based Learning-based engineering drawings. The research method used to develop this module is the Research and Development version of Borg and Gall simplified by Anik Ghufron, Anik Ghufron's simplified Borg and Gall development model has four steps: 1) Preliminary Research, 2) Development, 3) Field Testing,4) Product Deployment. This study uses one way of collecting data in the form of validation questionnaires. The results showed that the module developed was declared feasible with the validity value of Materials Specialist 3.16 and Media Expert 3.67. The data obtained shows that Visual Basic learning modules and resulting problem-based learning images can be executed.